Analisis Learning Obstacle Materi Persamaan Garis Lurus pada Siswa - Islamiati, Puan Amalia; Sumiaty, Encum (Jurnal Pendidikan Matematika : Judika Education, 2024)
The primary objective of this study is to identify and examine the learning obstacles by students when learning about linear equations. Employing a qualitative methodology, the research incorporates triangulation as means of data collection, involving classroom observations, analysis of tests, as well as interviews with both students and teachers. The participants in this study were eight grade students from a specific area. Findings reveal several common learning obstacles encountered by students in grappling with straight line equations. Among these challenges, a primary issue is the insufficient grasp of fundamental algebraic concepts, including the comprehension of variables and coefficients within equations. Furthermore, difficulties arise in visualizing the correlation between straight line equations and their graphical representations, along with applying appropriate problem-solving methods. The conclusions drawn from this research offer insights into the impediments students face in learning straight line equations. To enhance student comprehension, it is suggested that educators focus on solidifying basic algebraic concepts, utilize supportive visual aids, and cultivate a learning environment that fosters students' motivation and enthusiasm towards mathematics. Keywords: Learning Obstacles, Triangulation, Linear Equations